2016
DOI: 10.1016/j.comppsych.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of emotional facial expressions in anxious and nonanxious depression

Abstract: Background Anxiety and depression have each been independently associated with impairments in emotional face recognition. However, little is known about the nature of these impairments when anxiety and depression co-occur. Methods This post-hoc analysis evaluated the relationship between anxiety status and performance on the Emotional Expression Multimorph Task within a clinical sample of individuals with major depressive disorder (MDD). Results Participants with anxious depression (n=14) and nonanxious de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Finally, high comorbidity between anxiety and mood disorders is another facet that may influence ES performance. A recent study on recognition of facial expressions in adults with comorbid depression and anxiety ( n = 14) compared to nonanxious depression ( n = 14) demonstrated that diminished sensitivity to happy and sad expressions was specific to anxious depression but not hypervigilance toward threatening facial expressions (Berg et al, ). In our sample, participants completed a GAD‐7 but no measures of depression, limiting our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, high comorbidity between anxiety and mood disorders is another facet that may influence ES performance. A recent study on recognition of facial expressions in adults with comorbid depression and anxiety ( n = 14) compared to nonanxious depression ( n = 14) demonstrated that diminished sensitivity to happy and sad expressions was specific to anxious depression but not hypervigilance toward threatening facial expressions (Berg et al, ). In our sample, participants completed a GAD‐7 but no measures of depression, limiting our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this slowed processing speed has been shown to effect executive functioning (Payne & Smith, 2014;Payne & Thompson, 2015;Sheppard & Vernon, 2008), such as those required to make judgments regarding emotional facial expressions. Depression is also a common comorbid disorder of SUDs (Davis, Uezato, Newell, & Frazier, 2008;Swendsen, & Merikangas, 2000;Currie, 2005), and interestingly, research has shown that those with depressive disorders also have deficits in their ability to accurately interpret negative emotional expressions (Berg, et al, 2016;Demenescu, Kortekaas, Boer, & Aleman, 2010;Csukly, et al, 2010). Future research should query this hypothesis further.…”
Section: Perceptual-attentional Processes: Viewing Timementioning
confidence: 99%
“…A great variety of studies show changes in the visual processing of patients with schizophrenia and depression. Among those are altered perceptual organization (Steven et al, 2020;Panton, Badcock, & Badcock, 2016;Silverstein & Keane, 2011), face perception and recognition (Frassle et al, 2020;Marosi, Fodor, & Csukly, 2019;Stroud et al, 2018;Chen & Ekstrom, 2017;Berg et al, 2016;Maher, Ekstrom, Holt, Ongur, & Chen, 2016;McBain, Norton, & Chen, 2010;Silverstein et al, 2014;Vakhrusheva, et al, 2014), Psicol. Pesqui.…”
Section: Palabras Clavementioning
confidence: 99%